Pharmacotherapeutic strategy for COPD patients: focus on dual bronchodilators - A. I. Sinopalnikov (Медицинский совет, 2021)
For two decades, the GOLD Initiative has consistently identified the use of bronchodilators as a priority in the pharmacotherapeutic strategy for COPD. The authors of international and national clinical guidelines consider fixed combinations of long-acting beta2-agonists (LABAs) and long-acting muscarinic receptor antagonists (LAMAs) as “first-line” drugs in most patients with COPD. Numerous clinical studies have shown that fixed LABAs/LAMAs combinations provide optimal bronchodilation and play a paramount role in preventing exacerbations of COPD. Outperforming placebo and active controls, LABAs, LAMAs, inhaled glucocorticosteroids (ICS)/LABAs combination bronchodilators may differ in their therapeutic potential. The available evidence base currently does not allow to make an unambiguous choice in favor of one or another fixed LABAs/ LAMAs combination. With the appearance of “triple” combinations (ICS/LABAs/LAMAs) on the pharmaceutical market, the issue of their comparison with “dual” bronchodilators has become particularly acute. Currently available data suggest that the use of “triple” therapy is not considered as a starting treatment option for COPD and is appropriate only in a subgroup of patients with a higher baseline risk of exacerbations: in the presence of a history of exacerbations ≥ 1, which required prescription of systemic antibiotics and/or glucocorticosteroids, or necessitated hospitalization during the previous year. Thus, ICS-containing therapy is justified only in cases of recurrent exacerbations of moderate COPD or single episodes of severe exacerbations, despite the continued administration of LABAs/LAMAs, as well as in certain categories of patients whose inflammatory profile suggests a “response” to ICS.